(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Introduction: Adolescence and young adulthood are critical periods of neurocognitive, psychological, and emotional development. In Assam, the rising prevalence of substance use among youth has become a pressing public health concern, shaped by rapid socio-cultural transitions and limited mental health awareness. Early initiation of substance use is strongly linked to impairments in attention, working memory, executive functioning, and emotion regulation. However, empirical evidence on these deficits among Assamese youth remains scarce. This study examined the cognitive and emotional regulation difficulties associated with Substance Use Disorder (SUD). Methodology: A cross-sectional, comparative study was conducted with 320 participants (160 youths with clinically identified SUD and 160 matched healthy controls). Substance use severity was assessed using WHO-ASSIST, emotion regulation with the Difficulties in Emotion Regulation Scale (DERS), and cognitive functioning with the Trail Making Test (TMT-A and TMT-B) and a Cognitive Assessment Questionnaire. Independent t-tests evaluated group differences, and MANOVA assessed multivariate effects of substance use on cognition. Results:Youths with Substance Use Disorder demonstrated significantly poorer cognitive performance across all measures compared to healthy controls (p<.001), with large effect sizes observed for attention, processing speed, and executive functioning. Deficits were particularly evident on TMT-A and TMT-B, indicating impairments in processing speed, cognitive flexibility, working memory, inhibitory control, and sustained attention. Additionally, youths with SUD reported significantly greater difficulties in emotion regulation, particularly in impulse control, goal-directed behavior, and emotional clarity (p<.001). Conclusion:Substance use among youths in Assam is associated with marked cognitive impairments and significant emotion regulation difficulties, highlighting the need for early screening, preventive strategies, and integrated interventions tailored to young populations.